Beyond blurred lines: rape culture in popular media - Phillips, Nickie D. (Rowman & Littlefield, 2017)
Acknowledgments -- Rape culture : the evolution of a concept -- The mainstreaming of rape culture -- "Hey TV stop raping women" -- Geek spaces : "pretty girls pretending to be geeks" -- Geek spaces : feminist interventions and "witch hunts" -- Rape culture on campus: "real men don't hurt women" -- Reconciling panic and policy -- Appendix -- Resources -- Index -- About the author